The gendered nature of asset accumulation in urban contexts: Longitudinal results from Guayaquil, Ecuador - Caroline Moser; Andrew Felton (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper examines the gendered nature of asset accumulation between 1978 and 2004 in Indio Guayas, a low-income community on the periphery of the city of Guayaquil, Ecuador. In so doing, it emphasizes both the importance of combining quantitative and qualitative intra-household data, as well as taking a longitudinal perspective rather than at a single point in time. This paper seeks to examine the relationship not only between gender and urban income poverty but also, more importantly, between gender and urban asset accumulation, illustrating how the combination of quantitative econometric measurement of assets and qualitative in-depth anthropological findings on the complex underlying gender relations both contribute to a far more comprehensive analysis of asset accumulation processes in urban contexts than can be gained from any single methodological approach.
Keywords: J16; O18; R51; 330; gender; assets; asset accumulation; urban; Ethnische Gruppe; Familiensoziologie; Vermögenszuwachs; Familienökonomik; Geschlechterforschung; Stadtregion; Ecuador